Validation of the Children’s Separation Anxiety Scale – Parent Version (CSAS-P) - Méndez, Xavier; Espada, José P.; Ortigosa, Juan M.; García-Fernández, José M. (Frontiers in Psychology, 2022)
The main objective of this research was to validate the parents’ version of the Children's Separation Anxiety Scale (CSAS-P), which assesses separation anxiety symptoms in pre-adolescence, the stage with the highest incidence of anxiety disorder due to separation. In Study 1, 1,089 parents, aged 26 to 59 years (M = 38.57, SD = 5.96), were selected by random cluster sampling, who completed the CSAS-P to obtain the factorial structure. Exploratory factor analysis identified four related factors: Worry about separation, Opposition to separation, Calm at separation, and Distress from separation, which explained 42.93% of the variance. In Study 2, 3,801 parents, aged 25 to 57 years (M = 37.23, SD = 5.48), completed the CSAS-P, and their children completed the Children’s Separation Anxiety Scale (CSAS). The four related-factor model from Study 1 was validated by confirmatory factor analysis. The CSAS-P had adequate internal consistency (α = 0.84), temporal stability (r = 0.72), and invariance across children’s age and gender and the parent who completed the scale. Age and gender differences were small: older children scored higher on Worry about separation and younger children on Distress from separation; the girls scored higher on all factors. Small differences were also found depending on the parent who completed the scale without finding a clear pattern. Parents scored significantly lower than the child on all four factors of the scale. The results support the reliability and validity of the CSAS-P, an instrument that complements the child's self-report in the framework of the multi-source assessment.